OPPORTUNITIES TO CREATE PRACTICAL WORKS OF ART IN MODERN MATERIALS - Abdijalilov Abdivokhid Abdikhalimovich (American Journals, 2022)
The works of applied art of Uzbekistan occurred in the initial stages of development of human society, caused by the need to satisfy the demands and needs of the people, the symbol of the centuries-old culture of the people, the expression of the artisans a wealth of experience in talent. Restoration works of applied art is one of the leading branches.
Keywords: preservation, repair, practical-decoration, works of art, applied art, conservation, correction, restoration.